Obama's America - Pedersen, Carl (Edinburgh University Press, 2009)
The year 2008 will be remembered as the moment when the US elected its first African American president. This revealing book seeks to place the extraordinary rise of Barack Obama within the larger context of a possible historic political realignment in the US and of limits to US power in the world. For 2008 also offered a number of history lessons that will surely inform studies of the election and its aftermath. Carl Pedersen's book is an attempt to engage with these history lessons. It examines the demographic changes that will likely change the nature of American national identity. And it assesses the extent to which the grassroots organizations that were crucial in winning the election for Obama may influence the way he will govern the nation. Obama's America also attempts to map out the contours of an Obama Doctrine in foreign policy by looking at how his identity has shaped his views on the role of the US in the world and how he, in turn, has been influenced by his foreign policy advisers. It examines the challenges Obama faces in confronting a post-American world in which the US is no longer the sole superpower. Will Obama be a transformative president?
Keywords: Obama, Barack.; Obama, Barack; United States -- Politics and government -- 2001-2009.; United States -- History -- 21st century.; Presidents -- United States -- Election -- 2008.; États-Unis -- Politique et gouvernement -- 2001-2009.; États-Unis -- Histoire -- 21e siècle.; HISTORY.; POLITICAL SCIENCE -- Political Process -- Leadership.; Politics and government; Presidents -- Election; United States; 2000-2099; Electronic books.; History